Cellular stress response, redox status, and vitagenes in glaucoma: a systemic oxidant disorder linked to Alzheimer’s disease - Trovato Salinaro, Angela; Cornelius, Carolin; Koverech, Guido; Koverech, Angela; Scuto, Maria; Lodato, Francesca; Fronte, Vincenzo; Muccilli, Vera; Reibaldi, Michele; Longo, Antonio; Uva, Maurizio G.; Calabrese, Vittorio (Frontiers in Pharmacology, 2014)
Amyloid deposits, constituted of amyloid beta (A) aggregates, are a characteristic feature of several neurodegenerative diseases, such as Alzheimer’s, mild cognitive impairment and Parkinson’s disease. They also have been recently implicated in the pathogenesis of retinal damage, as well as age-related macular degeneration and glaucoma. Glaucoma is a progressive optic neuropathy characterized by gradual degeneration of neuronal tissue due to retinal ganglion cell loss, associated to visual field loss over time resulting in irreversible blindness. Accumulation of Aβ characterizes glaucoma as a protein misfolding disease, suggesting a pathogenic role for oxidative stress in the pathogenesis of retinal degenerative damage associated to glaucoma. There is a growing body of evidence demonstrating a link between Alzheimer’s disease and glaucoma. Further, several Hsps members have been implicated both in neurodegenerative diseases and glaucomatous apoptosis. To maintain redox homeostasis vitagenes, as integrated mechanisms, operate actively to preserve cell survival under condition of stress. Vitagenes encode for sirtuin, thioredoxin and heat shock proteins. The present study was designed to investigate cellular stress response mechanisms in the blood of patients with glaucoma, compared to control subjects. Levels of vitagenes Hsp72, HO-1, as well as F2-isoprostanes were significantly higher in the blood of patients with glaucoma than in controls. Furthermore, in the same experimental group increased expression of Trx and sirtuin 1 were measured. Our results sustain the importance of redox homeostasis disruption in the pathogenesis of glaucoma and highlights the opportunity that new therapies that prevents neurodegeneration through non-immunomodulatory mechanisms might be synergistically associated with current glaucoma therapies, thus unravelling important targets for novel cytoprotective strategies.